MANAGEMENT OF THE DISTANCE EDUCATION PROCESS IN HIGHER EDUCATION (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the effective management of distance education processes in Uzbekistan’s higher education system. In the wake of global digital transformation and the COVID-19 pandemic, distance education has emerged as a key tool for maintaining the continuity of learning. However, its success depends not only on technological infrastructure but also on how well the process is managed. The study analyzes core management functions—planning, organizing, monitoring, and quality assurance—within the context of digital education. It also explores the use of artificial intelligence tools, digital platforms, development of educators’ digital competencies, and improvements to educational infrastructure. The author concludes that systematic management of distance learning can enhance quality, accessibility, and continuity in higher education.